COMPENSATING WAGES OF AGROCHEMICAL EXPOSURE RISKS OF COCOA FARMWORKERS - Damilare FADIJI; Luke OKOJIE; Dare AKERELE; Jefferson OKOJIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Occupational risk is a major factor reducing productivity of farm workers as it impairs their physical capacity and increase their vulnerability to ill health, diseases and injuries. Agrochemical exposure risk has been attributed to work demand and unhealthy work environment that these workers are subjected to which they are often not compensated. Consequently, this study estimated the compensating wages of life quality for agrochemical exposure risks of cocoa farm workers in Idanre Local Government Area, Ondo State, Nigeria. Multistage sampling technique was used to select 180 cocoa farm workers while data on factors affecting agrochemical exposure risks. Data were analyzed using descriptive statistics and linear hedonic regression. Linear hedonic regression revealed that temperature (β = 5.02), health index (β = 9.65) and participating in agrochemical spraying (β = 44.71) had positive and significant (p<0.05) influence on compensating wages while smoking (β = -41.77) and use of personal protective gadgets during spraying (β = -31.67) had negative and significant (p<0.05) influence. Cocoa farm workers received ₦75.00k per day as the compensation for incurring occupational risks. The study concluded that appropriate use of personal protective equipment minimizes agrochemical exposure risks. It was therefore recommended that educational programs that will enhance farmer’s knowledge, skills and attitude to adopt safety measures in pesticide usage should be adequately planned.